Luigi Nono: como una ola de fuerza y lus - Nono, Luigi 1924-1990; Assis, Paulo de; Barainsky, Claudia; Michiels, Jan; WDR Sinfonieorchester (Cologne, Germany); Rundel, Peter; Warinsky, Léo (Vienna Paladino media gmbh, 2018)
CD and booklet (23 pages), published by KairosComo una ola de fuerza y luz (1971-72) is the culmination of Luigi Nono's politically engaged compositional phase, while .....sofferte onde serene... (1975-77) marks the beginning of a subtle and serene new aesthetic orientation. Both works are presented here in highly expressive interpretations that give special attention to the tape parts, revealing many previously unheard sonic materials. Most importantly, the recording of .....sofferte onde serene... uses a newly produced reconstruction of the original stereo tape, which has not been available since Maurizio Pollini's first recording. Composed after a period of profound study of Nono's sketches and compositional techniques, Paulo de Assis's unfolding waves& con luigi nono (2012) is a reflection on "listening" through the exploration of multiple temporalities, fragmented timbres, indiscernible sounds, and labyrinthine movements of sound in space.Luigi Nono Como una ola de fuerza y luz for soprano, piano, orchestra and tape 1. Invocation and lamentation of Luciano 06:32 2. Luciano's presence in his absence 09:02 3. The Long March 09:59 4. Collective explosion in the certainty of Luciano's absence 04:45Luigi Nono 5. ..... sofferte ond serene ... 13:55Paulo de Assis 6. unfolding waves... con luigi nono for orchestra and three instrumental groups 14:08